Cover. Issue 7 (4th June 2022) - Liang, Xiyun; Chen, Peikai; Chen, Chao; Che, Wei; Yang, Yue; Tan, Zhijia; Li, Hechun; Zhou, Yapeng; Yin, Shijie; To, Michael Kai‐tsun; Niu, Qiang
Abstract : The cover image is based on the Research Report Comprehensive risk assessments and anesthetic management for children with osteogenesis imperfecta: A retrospective review of 252 orthopedic procedures over 5 years by Xiyun Liang et al., https://doi.org/10.1111/pan.14454 .